2018
DOI: 10.1103/physrevmaterials.2.115002
|View full text |Cite
|
Sign up to set email alerts
|

Routes for increasing endurance and retention in HfO2 -based resistive switching memories

Abstract: We investigate metastable and thermodynamically stable phases that can be expected to occur in electroformed filaments in resistively switching hafnia, and discuss their relevance for the switching process. To this end, we conduct a study, based on density functional theory combined with an evolutionary algorithm determining the composition-dependent (meta)stable phases in HfO x , focusing on the region 0 < x < 2. We find that oxygen vacancies in hafnia tend to form regular patterns, which leads to periodic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…Furthermore, the formation of oxygen-rich hexagonal hafnium oxide was predicted by several authors. 22,24,25 While the value of the "band gap" between O 2p and the conduction band can only be estimated for hcp-HfO 0.7 (as the optical baseline signal was too intense for this sample), the trend of the other samples suggests a constant value of ∼5.6 eV. Further, the XPS valence spectra (see Figure 7c) indicate a similar value for the Fermi level position of ∼4.3 eV above the O 2p band.…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, the formation of oxygen-rich hexagonal hafnium oxide was predicted by several authors. 22,24,25 While the value of the "band gap" between O 2p and the conduction band can only be estimated for hcp-HfO 0.7 (as the optical baseline signal was too intense for this sample), the trend of the other samples suggests a constant value of ∼5.6 eV. Further, the XPS valence spectra (see Figure 7c) indicate a similar value for the Fermi level position of ∼4.3 eV above the O 2p band.…”
Section: Resultsmentioning
confidence: 83%
“…[326,327] Therefore, the formation of o-phase-a metastable phase in HfO 2 -based material-can be driven by manipulating the energy landscape during the fabrication process. The capsulation of HfO 2 thin film before the annealing procedure is indeed only one method to stabilize o-phase, and it is a wellestablished fact that the total energy of thin films can be strongly affected by the grain boundaries, [328,329] film thickness, [330][331][332] point defects (especially oxygen vacancies in case of oxide thin films), [333][334][335][336][337][338][339][340][341][342][343][344][345] film composition, [346][347][348][349][350][351] the type of capping electrode, [326,327] and deposition and annealing conditions. [311,314,332] During the last decade, numerous investigations were conducted to understand the formation of the o-phase and optimize the fabrication conditions to provide a driving force toward stabilization of the o-phase.…”
Section: Origin Of Ferroelectricity In Hafnium Oxidementioning
confidence: 99%
“…[ 333 ] Therefore, controlling oxygen vacancies is a vital part of the device lifetime. Rushchanskii et al [ 335 ] integrated DFT with an evolutionary algorithm and found that oxygen vacancies in HfO 2‐ x tend to cluster in the form of 2D extended defects, revealing several patterns of local relative arrangements that may result in polar m structures. They showed that under normal conditions, oxygen vacancies in the bulk material do not lead to the stabilization of the o ‐phase; however, the presence of a limited number of oxygen vacancies in HfO 2 results in a polar structure already in m ‐phase.…”
Section: Parameters Influencing the Ferroelectric Propertiesmentioning
confidence: 99%
“…the effect of oxygen vacancies in phase stabilization of HfO2 is studied, the polar o-phase sits in between the m-and t-phase, where m-has the lowest oxygen vacancies concentration. 10 Coherently with the latter, it has been reported that the redistribution of defects, particularly oxygen vacancies, by application of wake-up cycling, can help to stabilize the ferroelectric orthorhombic structure through field-induced phase transformation. 61 Often, the oxygen vacancies (which in this material are known to be positively charged) are generated near the electrode interfaces, or migrate there upon the application of the electric field.…”
Section: Ferroelectric Wake-up Conditioningmentioning
confidence: 97%